Quantification of paravertebral cross-sectional muscle areas and fatty degeneration and their correlation with clinical parameters in ankylosing spondylitis: a comprehensive analysis - Selçuk Akkaya; Gonca Sağlam Akkaya; Serpil Demirulus; Hanife Baykal Şahin; Gamze Kılıç; Erhan Çapkın; Murat Karkucak (ARP Rheumatology, 2025)
Aims: Ankylosing spondylitis (AS) is a chronic disease characterized by inflammation of the spine and joints. This study aimed to examine the multifidus (MF) and erector spinae (ES) muscles in AS patients using magnetic resonance imaging (MRI), and to evaluate the clinical implications of muscle findings. Methods: This study included 43 patients and 40 matched controls. The total (TCSA), functional (FCSA), relative CSAs, and ratios of MF and ES muscles were compared between the groups. The Visual Analog Scale, Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index (BASFI), Ankylosing Spondylitis Disease Activity Score with CRP, Ankylosing Spondylitis Disease Activity Score with ESR, Bath Ankylosing Spondylitis Activity Index, and Ankylosing Spondylitis Quality of Life Questionnaire (ASQoL) scores of AS patients were recorded. Comparisons between the two groups were made using the Student's t-test and the Mann-Whitney U test.